Syntrophic Growth of Biomaibacter acetigenes Strain SP2 on Lactate and Glycerol - Sofiya Parshina; Elena Zhuravleva; Anna A. Nikitina; Denis Grouzdev; Nadezhda Kostrikina; Vadim Kevbrin; Andrey Novikov; Dmitry Kopitsyn; Tatyana Kolganova; Roman Baslerov; Alla N. Nozhevnikova; Yuriy Litti (Fermentation, 2023)
A moderately thermophilic Gram-positive chemo-organotrophic bacterium, strain SP2, was isolated by serial dilutions with crotonate and yeast extract as substrates from a butyrate-degrading methanogenic enrichment obtained from thermophilically digested sludge of the Kuryanoskaya wastewater treatment plant (Moscow, Russia). Cells of strain SP2 are spore-forming rods, sometimes occurring in short chains. The bacterium is an obligate anaerobe that grows at temperatures from 20 to 70 °C (55–60 °C optimum) within a pH range of 3.5–8 (7.5 optimum) and with NaCl concentrations of up to 2.5%. The strain utilized yeast extract and simple sugars as carbon and energy sources. Thiosulfate was used as an electron acceptor when grown on sucrose, resulting in the formation of hydrogen sulfide and the accumulation of elemental sulfur globules inside the cells. Strain SP2 is phylogenetically related to Biomaibacter acetigenes strain SK-G1T as revealed by comparison with the 16S rRNA gene (99.9% identity) and genome (ANI 99%, dDDH 90%) of both strains. It is interesting that strain SP2 was capable of syntrophic conversion of glycerol and lactate when co-cultivated with hydrogenotrophic methanogen, which was not previously shown for the SK-G1T type of strain. The isolation and in-depth study of new facultatively syntrophic microorganisms is important for wastewater treatment ecotechnologies due to their ability to switch to an alternative source of carbon and energy and therefore greater resistance to changing environmental conditions in bioreactors.